Influence of Gender Bias on Distribution of Hybrid Sterility in Rice - Zin Mar Myint,; Koide, Yohei (Frontiers in Plant Science, 2022)
Hybrid sterility genes define species identities, setting reproductive barriers between distantly related Oryza relatives. They induce allelic-specific selective gametic abnormalities by killing pollens, embryo sacs or both, and thus resulting in the male specific transmission ratio distortion (mTRD), female specific transmission ratio distortion (fTRD), and or sex-independent transmission ratio distortion (siTRD) in hybrids. Although more than 50 hybrid sterility genes have been reported, comprehensive analysis on the distributional pattern of TRD systems in Oryza species is limited. In this review, we surveyed the TRD systems and the underlying possible mechanisms in these species. In rice, pollen killers which cause mTRD are often observed in higher frequency than egg killers and gamete eliminators which are factors affecting fTRD and siTRD respectively. Due to the rather massive population of pollen grains, their reduction in the number caused by hybrid sterility possesses a smaller selective disadvantage to the hybrid individuals, in contrast to female gamete abortion. The pattern of TRD distribution displays less abundancy of siTRD. It suggests that fixation of siTRD might require a certain time rather than single sex-specific factors. The presence of linked sterility factors worked for mTRD and fTRD, and strength of their linkage in chromosomal regions might determine the type of sterility and TRD. The study of TRD systems has a potential to reveal the relationships between selfish genes and their functions for reproductive isolation.